2017
DOI: 10.1111/iar.12201
|View full text |Cite
|
Sign up to set email alerts
|

Rapid cooling and geospeedometry of granitic rocks exhumation within a volcanic arc: A case study from the Central Slovakian Neovolcanic Field (Western Carpathians)

Abstract: U–Pb Sensitive High‐Resolution Ion MicroProbe (SHRIMP) dating of zircon in combination with (U–Th)/He dating of zircon and apatite is applied to constrain the emplacement and exhumation history of the youngest granitic rocks in the Western Carpathians collected in the Central Slovakian Neovolcanic Field. Two samples of diorite from the locality Banky, and granodiorite from Banská Hodruša yield the U–Pb zircon concordia ages of 15.21 ±0.19 Ma and 12.92 ±0.27 Ma, respectively, recording the time of zircon crysta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
(61 reference statements)
0
3
0
Order By: Relevance
“…A projection in Sr-Nd isotope space (Figure 13) with variable Sr contamination likely implies a composition similar to the mafic "granulite" xenoliths from the WPB and, thus, a more depleted mantle source for the SRM magmas than for the alkaline CPR 87 Sr/ 86 Sr contamination on the SRM volcanic rocks. Sources of 87 Sr/ 86 Sr and 143 Nd/ 144 Nd isotope data from the CPR are summarized in [14,[16][17][18][19][20][21][22]24,25,27,29,30,[35][36][37][38]40,43,44,90,91,95,[97][98][99][100][101][102][103][104][105][106][107].…”
Section: Geochemistry and Inferred Melted Mantle Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…A projection in Sr-Nd isotope space (Figure 13) with variable Sr contamination likely implies a composition similar to the mafic "granulite" xenoliths from the WPB and, thus, a more depleted mantle source for the SRM magmas than for the alkaline CPR 87 Sr/ 86 Sr contamination on the SRM volcanic rocks. Sources of 87 Sr/ 86 Sr and 143 Nd/ 144 Nd isotope data from the CPR are summarized in [14,[16][17][18][19][20][21][22]24,25,27,29,30,[35][36][37][38]40,43,44,90,91,95,[97][98][99][100][101][102][103][104][105][106][107].…”
Section: Geochemistry and Inferred Melted Mantle Sourcesmentioning
confidence: 99%
“…The dashed arrow shows the effect of87 Sr/86 Sr contamination on the SRM volcanic rocks. Sources of87 Sr/86 Sr and 143 Nd/ 144 Nd isotope data from the CPR are summarized in[14,[16][17][18][19][20][21][22]24,25,27,29,30,[35][36][37][38]40,43,44,90,91,95,[97][98][99][100][101][102][103][104][105][106][107].…”
mentioning
confidence: 99%
“…Along many volcanic arcs it has been demonstrated that active volcanoes were emplaced in their own metamorphosed magmatic basement that was promptly exhumed (Kuril: De Grave et al., 2016; Lesser Antilles: Favier et al., 2019). It is noteworthy that during arc migration, cooling of an arc pluton might be interpreted to record its exhumation, whereas it might be associated with a drop in the paleo‐geothermal gradient due to volcanic arc cessation (Kohút & Danišík, 2017). However, the effects on thermochronological ages of the evolution through time of the thermal structure of the crust can be investigated using a numerical modeling approach.…”
Section: Introductionmentioning
confidence: 99%